Implementation of the Independent Campus Learning Program in 2021 (Case Study of the Teaching Campus Program in SMP Negeri 4 Setu) - Samsul Ode; Megayanti Afrilia (Budapest International Research and Critics University, 2022)
Education and literacy skills are two very important things in our lives. The progress of a country directly depends on the literacy rate in that country. Educated people are expected to do their job well. Several educational problems in Indonesia, such as the uneven distribution of education, the limited quality of teachers and the low literacy of numeracy, have prevented Indonesia's position from becoming a country with high quality education. The Teaching Campus Program Batch 2 of 2021, which was initiated by the government, is one of the MBKM programs that focuses on increasing numeracy literacy skills in primary and junior secondary education. This context is getting stronger considering the condition of literacy and numeracy in Indonesia which is still low. In line with this reality, the government is making efforts to increase literacy and numeracy as one of the national priority agendas. This study aims to determine the implementation of the numeracy literacy program at SMP Negeri 4 Setu as part of the teaching campus program. The method in this study uses qualitative methods through interview techniques, observation and quantitative data collection through questionnaires. SMP Negeri 4 Setu, Bekasi Regency, West Java Province, became a research site for about five months starting from August 3 to December 16, 2021. The results showed that the numeracy literacy program was quite satisfactory because this program could increase interest in numeracy literacy. The researcher gives suggestions for this program to immediately update the data in DAPODIK so that the recipients of this program are right on target.